The stolen queen eaudiobook A novel. - Davis, Fiona (Books on Tape, 2025)
*A New York Times Bestseller* From New York Times bestselling author Fiona Davis, an utterly addictive new novel that will transport you from New York City’s most glamorous party to the labyrinth streets of Cairo and back. Egypt, 1936: When anthropology student Charlotte Cross is offered a coveted spot on an archaeological dig in Egypt’s Valley of the Kings, she leaps at the opportunity. That is until an unbearable tragedy strikes. New York City, 1978: Nineteen-year-old Annie Jenkins is thrilled when she lands an opportunity to work for former Vogue fashion editor Diana Vreeland, who’s in the midst of organizing the famous Met Gala, hosted at the museum and known across the city as the “party of the year.” Meanwhile, Charlotte is now leading a quiet life as the associate curator of the Met’s celebrated Department of Egyptian Art. She’s consumed by her research on Hathorkare—a rare female pharaoh dismissed by most other Egyptologists as unimportant. The night of the gala: One of the Egyptian art collection’s most valuable artifacts goes missing, and there are signs Hathorkare’s legendary curse might be reawakening. Annie and Charlotte team up to search for the missing antiquity, and a desperate hunch leads the unlikely duo to one place Charlotte swore she’d never return: Egypt. But if they have any hope of finding the artifact, Charlotte will need to confront the demons of her past—which may mean leading them both directly into danger.